If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+15-9=-2x+16
We move all terms to the left:
3x+15-9-(-2x+16)=0
We add all the numbers together, and all the variables
3x-(-2x+16)+6=0
We get rid of parentheses
3x+2x-16+6=0
We add all the numbers together, and all the variables
5x-10=0
We move all terms containing x to the left, all other terms to the right
5x=10
x=10/5
x=2
| -77=7n | | n10=4 | | 1/2+6z=8/10 | | 132+x=54 | | 6m+3m+2m-11m+2m=10 | | -5(10+6x)=220 | | 50+(x+80)+(x+20)=180 | | 10(5h-4)=60 | | U-7=2u | | 5÷x=20 | | 1x-3x-6=4x+24 | | -1.5-6x-1.8-2x=-7x-2.9 | | 1x+3=3x+-1 | | -3(r-5)=-6+2(7r+2) | | 3x12=3(x+1)-15 | | 7m-(5m-12)=8+2m+4 | | 4(2x-5)^3+7(2x-5)^2=0 | | 11+a=-23 | | x2=361. | | 1x+3=3x-1 | | 7(z+4)=z-8 | | 8-(3x-9)=8-4x | | 5/2yy=10 | | 14x+4=8x | | m+2=16-m | | –11+x=38 | | -2x+6=8* | | 30=14-2a | | 6z-3-4z=9 | | m-20=-34 | | 7+18x=115 | | -12x+6–3=3x+48 |